Onomastic achievements of Professor Witold Mańczak (1924–2016) (Geographical names in physical space, 2016)
This memory of Professor Witold Mańczak deceased in 2016, presents the cv and the most important onomastic achievements of the outstanding and appreciated Polish linguist, who dedicated his scientific life to the study of different European languages and created some valuable theories concerning the evolution of languages, the etymology and the nature of proper names.